Fonda San Miguel : forty years of food and art - Gilliland, Tom, 1938-; Ravago, Miguel (University of Texas Press, 2016)
Updated and reissued to celebrate the restaurant's four decades of success, Fonda San Miguel presents more than one hundred recipes. The selections include many of Fonda's signature dishes -- Ceviche Veracruzano, Enchiladas Suizas, Cochinita Pibil, Pescado Tikin Xik, and Carne Asada -- as well as a delicious assortment of dishes from Mexico's diverse regional cuisines. Supplementary sections contain tips on buying and cooking with the various chiles and other ingredients, along with information on basic preparation techniques, equipment, and mail-order sources. Full-color photographs illustrate special dishes, and representative works from the impressive Fonda San Miguel art collection are also featured, along with notes on the artists.